2016
DOI: 10.1016/j.psyneuen.2016.03.016
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sex and irritable bowel syndrome on HPA axis response and peripheral glucocorticoid receptor expression

Abstract: Background and aims Dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis has been reported in irritable bowel syndrome (IBS). Enhanced HPA axis response has been associated with reduced glucocorticoid receptor (GR) mediated negative feedback inhibition. We aimed to study the effects of IBS status, sex, or presence of early adverse life events (EAL) on the cortisol response to corticotropin-releasing factor (CRF) and adrenocorticotropic hormone (ACTH), and on GR mRNA expression in peripheral blood mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 47 publications
2
42
0
Order By: Relevance
“…We found a significant interaction between IBS status, resilience, and the stress hormone response, particularly the cortisol response to ACTH stimulation and the recovery of cortisol levels to baseline. We have previously shown that the ACTH‐stimulated cortisol response is divergent with greater responses in IBS men vs HC men and a blunted response in IBS women vs HC women . In prior studies evaluating the relationship between resilience and HPA axis response, more resilient healthy individuals were found to have lower cortisol levels in response to a psychosocial stressor .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We found a significant interaction between IBS status, resilience, and the stress hormone response, particularly the cortisol response to ACTH stimulation and the recovery of cortisol levels to baseline. We have previously shown that the ACTH‐stimulated cortisol response is divergent with greater responses in IBS men vs HC men and a blunted response in IBS women vs HC women . In prior studies evaluating the relationship between resilience and HPA axis response, more resilient healthy individuals were found to have lower cortisol levels in response to a psychosocial stressor .…”
Section: Discussionmentioning
confidence: 96%
“…A subset of patients who completed the resilience questionnaires underwent tests to measure the HPA axis response to a hormone challenge. The results of the hormone challenge tests in a larger group of IBS and HC subjects were previously published …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An exacerbated HPA axis in IBS patients after hormone challenge correlated with visceral pain and a reduction in GR protein expression in peripheral blood mononuclear cells. 44 Although, it has been shown in adult rats that an early life stress evokes a change of GR expression in the hippocampus and central amygdala, 45,46 which enhances an activation of somatosensory area and visceral hypersensitivity. 47 Moreover, in postnatal day 10, a single stress session for 4 hours induced an alteration of GR expression in the colon in pups, weakened the intestinal barrier integrity allowing bacterial translocation, 48 and subsequently provoked later visceral hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…As is usually done for genetic association studies, we controlled for race and sex (Cross et al, 2010). Furthermore, there is evidence of sex differences in IBS symptoms (Houghton et al, 2016) and neurobiologic mechanisms including the HPA axis response (Videlock et al, 2016). In addition, we also controlled for anxiety and depression symptom scores because these are often higher in IBS subjects vs. HCs and CRH-R1 and their SNPs have been associated with anxiety and depression (Bradley et al, 2008; Fond et al, 2014) (Heim et al, 2009) (Papiol et al, 2007) (Park et al, 2013) (Sumner et al, 2014).…”
Section: Methodsmentioning
confidence: 99%